Ligamentum Flavum Hematoma Associated with L5–S1 Pars Interarticularis Defect: A Case Report and Review of the Literature - Kıbıcı, Kenan; Erok, Berrin; Çolak, Ahmet (Indian Journal of Neurosurgery, 2020)
Ligamentum flavum hematoma (LFH) is an extremely rare compressive epidural lesion of the spine. The clinical manifestations of LFH are similar to that caused by other more common pathologies of nerve root compression like disc herniation. In the diagnosis, magnetic resonance imaging (MRI) is very important but challenging due to the changing intensities of the hematoma in relation to the stages of the aging blood. Herein, we report a case of LFH compressing the spinal canal in a 60-year-old man with pars interarticularis defect. He presented with low back pain radiating to the left leg. The neurological examination was consistent with left S1 nerve root compression. The MRI revealed a left posterior epidural mass compressing the thecal sac and S1 nerve root at the left L5–S1 level near the pars interarticularis defect. After surgical removal of the lesion, histopathological examination confirmed the diagnosis of LFH. Following surgery, he recovered rapidly. LFH due to spinal instability is important in terms of the understanding of the pathophysiological mechanisms related with LFH.
Keywords: ligamentum flavum hematoma; radiculopathy; pars interarticularis defect; spinal instability